PENGARUH LIMBAH KULIT KOPI (Coffea sp) PENGOLAHAN SEDERHANA DENGAN LEVEL SUBSTITUSI SEBAGIAN JAGUNG TERHADAP PERSENTASE ORGAN DALAM AYAM PEDAGING - Palapa, Melisa; Tangkau, L.M.S; Montong, P.R.R.I.; Poli, Z. (Universitas Sam Ratulangi, 2020)
EEFCT OF COFFEE HUSK WASTE PRODUCT TREATED BY SIMPLE PROCESSING SUBSTITUTED WITH PART OF CORN IN RATION ON PERCENTAGE OF BROILER INTERNAL ORGAN. This study was conducted to evaluate the use of coffee husk waste product treated by simple processing substituted with part of corn in ration on percentage of broiler internal organ. Study was applied at Faculty of Animal Science, Sam Ratulangi University during 35 days. Total of 144 day old chick unsexed broilers, strain of CP 707, involving 36 experimental units of battery pens were used in this study. Each unit of pen was filled 4 birds under completely randomized design on factorial patter of 3x4. Factor A was focused on three processing treatments including coffee husk heated under sun light (A1), coffee husk immersed in the water (A2), and coffee husk boiled under water (A3). Factor B was focused on four treatments of substitution levels including ration containing corn without coffee husk substitution (B0), ration containing corn substituted with 25% coffee husk (B1), ration containing corn substituted with 50% coffee husk(B2), ration containing corn substituted with 75% coffee husk (B3). Analysis of variance showed that interaction of processing treatments did not affect significantly on the percentages of lung, heart and gizzard. This study indicated that simple processing of coffee husk were not affected the percentages of broiler internal organ. The substitution levels significantly affected percentage of internal organ. Percentages of lung, heart and gizzard were 1.38-1.86%, 0.31-0.72% and 1.6-2.77%, respectively. This study showed that utilization of coffee husk waste product by above simple processing could substitute part of corn in ration of 25% producing high percentage of broiler internal organ. Keywords: Broiler, Coffee husk by product, broiler internal organ